Deuterium and 15N fractionation in N2H+ during the formation of a Sun-like star. Issue 2 (9th February 2018) - De Simone, M; Fontani, F; Codella, C; Ceccarelli, C; Lefloch, B; Bachiller, R; López-Sepulcre, A; Caux, E; Vastel, C; Soldateschi, J
Abstract: Although chemical models predict that the deuterium fractionation in N2 H + is a good evolutionary tracer in the star formation process, the fractionation of nitrogen is still a poorly understood process. Recent models have questioned the similar evolutionary trend expected for the two fractionation mechanisms in N2 H +, based on a classical scenario in which ion-neutral reactions occurring in cold gas should have caused an enhancement of the abundance of N2 D +, 15 NNH +, and N 15 NH + . In the framework of the ASAI IRAM-30m large program, we have investigated the fractionation of deuterium and 15 N in N2 H + in the best known representatives of the different evolutionary stages of the Sun-like star formation process. The goal is to ultimately confirm (or deny) the classical 'ion-neutral reactions' scenario that predicts a similar trend for D and 15 N fractionation. We do not find any evolutionary trend of the 14 N/ 15 N ratio from both the 15 NNH + and N 15 NH + isotopologues. Therefore, our findings confirm that, during the formation of a Sun-like star, the core evolution is irrelevant in the fractionation of 15 N. The independence of the 14 N/ 15 N ratio with time, found also in high-mass star-forming cores, indicates that the enrichment in 15 N revealed in comets and protoplanetary discs is unlikely to happen at core scales. Nevertheless, we have firmly confirmed the evolutionary trend expected for the H/D ratio, with the N2 H + /N2 D + ratio decreasing before the pre-stellar core phase, and increasing monotonically during the protostellar phase. We have also confirmed clearly that the two fractionation mechanisms are not related.